Prevalence and risk factors of sexually transmitted infections among French service members - Duron, Sandrine (PLoS One, 2018)
INTRODUCTION: Sexually Transmitted Infections (STIs) have always represented a public health concern in the military, yet most studies rely on self-reports among non-random samples of military populations. In addition, most of the studies exploring STI rates among the military focus on US service members. This paper assesses the prevalence and correlates of STIs in the French military using biomarkers and compares self-reported versus diagnosed STIs. METHODS: Data are drawn from the COSEMIL study, a national sexual health survey conducted in the French military in 2014 and 2015. A random sample of 784 men and 141 women aged 18–57 years completed a self-administered questionnaire and provided biological samples for STI testing. We used logistic regression modeling to identify the correlates of STI diagnosis and self-reports. RESULTS: The prevalence of diagnosed STIs was 4.7% [3.8–5.9], mostly due to Chlamydia trachomatis. This rate was four times higher than the 12 months self-reported rate of 1.1% [0.6–2.3]. Reported STI rates were similar among men and women (1.1% versus 1.8%), but diagnosed STI rates were twice as high among females versus males (10.4% versus 4.1%, p = 0.007). There were significant differences in the determinants of reported versus diagnosed STIs. In particular, age and sexual orientation were associated with reported STIs, but not with diagnosed STIs. Conversely, STI counseling and depression were associated with STI diagnosis but not with STI reports. CONCLUSION: This study underlines the need to use biomarkers in population-based surveys, given the differential and substantial underreporting of STIs. Results also highlight the need for programmatic adaptation to address gender inequalities in STI rates, by developing women’s health services in the French military. Addressing such needs not only benefits women but could also serve as a strategy to reduce overall STI rates as most military women have military partners, increasing the risk of internal transmission.